1989
DOI: 10.1021/bi00444a041
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of bovine transducin: probing the GTP-binding site with affinity analogs

Abstract: The structure of the GTP-binding site of transducin, a signal-transducing G-protein involved in the visual excitation process, was studied by affinity labeling. Radioactive GTP analogues with reactive groups attached to different moieties of the GTP molecule were obtained and include 8-azido-GTP, P3-(4-azidoanilino)-P1-5'-GTP (AA-GTP), 5'-[p-(fluorosulfonyl)benzoyl]guanosine (FSBG), 3'-O-(3-[N-(4-azido-2-nitrophenyl)amino]propionyl)-GTP (ANPAP-GTP), the 2',3'-dialdehyde derivative of GTP (oGTP), and a bifuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Recent evidence indicates that G proteins may form polymers with the same or different subspecies (Hatta et al ., 1986;Hingorani et al, 1989;Nakamura and Rodbell, 1990 ;Vaillancourt et al, 1990) . Moreover, guanine nucleotide transfer between G, and G, has been demonstrated (Hatta et al, 1986) .…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that G proteins may form polymers with the same or different subspecies (Hatta et al ., 1986;Hingorani et al, 1989;Nakamura and Rodbell, 1990 ;Vaillancourt et al, 1990) . Moreover, guanine nucleotide transfer between G, and G, has been demonstrated (Hatta et al, 1986) .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a similar GTP derivative was unable to label the visual G-protein transducin [8]. In the present work, m-aminoacetophenone was attached to GTP via the y-phosphate, as previous work [4] suggested that modification at this position does not disturb binding to G-proteins, the coupling of the anilide to the Assay of adenylate cyclase activity Turkey erythrocytes [10] and rat parotid [11] membranes were prepared as previously described.…”
Section: Introductionmentioning
confidence: 98%
“…Consequently, nicotinamide-analogs with vibrational probes attached to the nicotinamide ring are likely to be able to report on the dynamics of the active sites of a wide variety of nicotinamide-dependent enzymes. Analogs of NAD + are widely used as mechanistic probes to understand enzymatic pathways, [42][43][44][45][46][47] and the idea of using a NAD-analog as a spectroscopic reporter holds great potential as a probe with widespread applications to many important enzymatic systems.…”
Section: Introductionmentioning
confidence: 99%